Evaluating the Psychometric Properties of the 7-Item Persian Game Addiction Scale for Iranian Adolescents - Lin, Chung-Ying; Imani, Vida; Broström, Anders; Årestedt, Kristofer; Pakpour, Amir H.; Griffiths, Mark D. (Frontiers in Psychology, 2019)
The 7-item Gaming Addiction Scale (GAS) is a brief instrument based on DSM criteria to assess gaming addiction. Although the psychometric properties of the GAS have been tested using classical test theory, its psychometric properties have never been tested using modern test theory (e.g., Rasch analysis). The present study used a large adolescent sample in Iran to test the psychometric properties of Persian GAS through both classical test and modern test theories. Adolescents (n = 4442; mean age = 15.3 years; 50.3% males) were recruited from Qazvin, Iran. In addition to the GAS, all of them completed the following instruments: the nine-item Internet Gaming Disorder Scale–Short Form (IGDS-SF9), Depression Anxiety Stress Scale (DASS), Pittsburgh Sleep Quality Index (PSQI), and a generic quality of life instrument. Two weeks later, all participants completed the GAS again. Confirmatory factor analysis (CFA) and Rasch analysis were used to test the unidimensionality of the GAS. Pearson correlation coefficients were used to test the test-retest reliability, and a regression model was used to test the criterion-related validity of the GAS. Both CFA and Rasch analysis supported the unidimensionality of the GAS. Pearson correlations coefficients showed satisfactory test-retest reliability of the GAS (r = 0.78 to 0.86), and the regression model demonstrated the criterion-related validity of the GAS (β = 0.31 with IGDS-SF9; 0.41 with PSQI). Based on the results, the Persian GAS is a reliable and valid instrument for healthcare providers to assess the level of gaming addiction among Persian-speaking adolescents.